Pengembangan Konten Media Sosial Di Balai Besar Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Mesin Dan Teknik Industri - Yayan Firmansyah; Raihana Rahiela (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
Balai Besar Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Mesin dan Teknik Industri (BBPPMPV BMTI) as an organisasi dan Unit Pelaksana Teknis (UPT) Kementerian Pendidikan dan Kebudayaan is an institution tasked with implementing education and training programs in the field of machinery and industrial engineering. Based on problem identification, information is obtained that BBPPMPV BMTI's social media needs to be optimized. This is indicated by the low engagement rate value. In an effort to increase the engagement rate value, the institution's social media content development is carried out, namely Facebook (Bbppmpv BMTI Kemdikbud), Instagram (@bmti.kemdikbud), and Twitter (@bmti_kemdikbud). The purpose of this project is to conduct planning, implementation, and evaluation on social media. The data collection method used in this project is the key informant interview method and STP (Segmenting, Targeting, Postioning) analysis analysis. The results of this project are 8 (eight) social media content and Instagram template designs from June 2023 to December 2023 accompanied by an e-manual book. The project success test through engagement rate analysis shows that after the content development is carried out, audience interaction with BPPMPV BMTI social media is in the above average or high category with the engagement rate value for Facebook is 6.72%, Instagram 4.42%, and Twitter 20.5%.